Analysing the EU Data Privacy Implications Resulting From Executive Order 14086: A Legal Perspective - Zoran Dimović (LeXonomica, 2024)
The exchange of personal data between the EU and the USA has sparked intense debates and contentious discussions. This heightened attention can be attributed to significant disparities in data privacy regulations between the two regions, as well as mounting concerns surrounding the potential misuse of personal information by U.S. companies and government entities. In response to these concerns, the EU implemented the GDPR in 2018, which introduced stringent regulations aimed at safeguarding data privacy. Additionally, the GDPR imposed restrictions on the transfer of personal data to countries outside the EU that lack comparable data protection measures. One of the prominent legal challenges in this context relates to concerns over the adequacy of data protection in the USA, particularly in light of U.S. surveillance programs and the potential for government access to personal data.PovzetekIzmenjava osebnih podatkov med EU in ZDA je sprožila intenzivne razprave. To povečano pozornost je mogoče pripisati velikim razlikam v predpisih o varstvu podatkov med obema regijama, pa tudi vse večji zaskrbljenosti glede morebitne zlorabe osebnih podatkov s strani ameriških podjetij in vladnih organov. Kot odgovor na te pomisleke je EU leta 2018 uvedla uredbo GDPR, s katero so bili uvedeni strogi predpisi, namenjeni varovanju zasebnosti podatkov. Poleg tega je uredba GDPR uvedla omejitve za prenos osebnih podatkov v države zunaj EU, ki nimajo primerljivih ukrepov za varstvo podatkov. Eden od vidnejših pravnih izzivov v tem okviru je povezan s pomisleki glede ustreznosti varstva podatkov v ZDA, zlasti v luči ameriških programov nadzora in možnosti vladnega dostopa do osebnih podatkov.